Altered Esophageal Mucosal Structure in Patients with Celiac Disease. (29th February 2016) - Pinto-Sánchez, María Inés; Nachman, Fabio D.; Fuxman, Claudia; Iantorno, Guido; Hwang, Hui Jer; Ditaranto, Andrés; Costa, Florencia; Longarini, Gabriela; Wang, Xuan Yu; Huang, Xianxi; Vázquez, Horacio; Moreno, María L.; et al.
Abstract : Background/Aim . Reflux symptoms (RS) are common in patients with celiac disease (CD), a chronic enteropathy that affects primarily the small intestine. We evaluated mucosal integrity and motility of the lower esophagus as mechanisms contributing to RS generation in patients with CD. Methods . We enrolled newly diagnosed CD patients with and without RS, nonceliac patients with classical reflux disease (GERD), and controls (without RS). Endoscopic biopsies from the distal esophagus were assessed for dilated intercellular space (DIS) by light microscopy and electron microscopy. Tight junction (TJ) mRNA proteins expression for zonula occludens-1 (ZO-1) and claudin-2 and claudin-3 (CLDN-2; CLDN-3) was determined using qRT-PCR. Results . DIS scores were higher in patients with active CD than in controls, but similar to GERD patients. The altered DIS was found even in CD patients without RS and normalized after one year of a gluten-free diet. CD patients with and without RS had lower expression of ZO-1 than controls. The expression of CLDN-2 and CLDN-3 was similar in CD and GERD patients. Conclusions . Our study shows that patients with active CD have altered esophageal mucosal integrity, independently of the presence of RS. The altered expression of ZO-1 may underlie loss of TJ integrity in the esophageal mucosa and may contribute to RS generation.